Electrical Engineering for Non-Electrical Engineers - Rauf S. B. Bobby (Library of Congress Cataloging-in-Publication Data)
This book is designed to serve as a resource for exploring and understanding basic electrical engineering concepts and principles, as well as related analytical and mathematical strategies. The author has structured and cross-referenced the material in a manner which facilitates quick study and comprehension, and serves to aid the reader in progressing and extending their fundamental electrical engineering knowledge. Topics include critical electrical engineering components of energy projects, electrical-related energy cost factors, tips on improvement of electrical energy intensity in industrial and commercial settings, an update on generation of electricity from renewal sources, basic principles of illumination and efficient lighting, and an explanation of important energy engineering terms and concepts. Also included is a discussion of the skills and preparation necessary for succeeding in the electrical engineering portions of various certification and licensure exams. Practical examples and case studies of electrical applications in industrial and commercial settings will be used to demonstrate the topics and procedures covered.